Penerapan Model Pembelajaran Problem Based Learning dalam Meningkatkan Pemahaman Konsep Siswa Pada Materi Genetika di MAS 1 Yaspi Labuhan Deli: (Problem Based Learning Model in Improving Student's Understanding of Concepts in Genetic Materials In MAS 1 Yaspi Labuhan Deli) - Windi Arningsih Nainggolan; Masdelina Sipahutar; Nurul Azmi Ramadhani; Olivia Erza Thania; Indayana Febriani Tanjung (BIODIK, 2023)
Problem based learning (PBL) is a learning model that is triggered by problems, which encourages students to learn and work cooperatively in groups to find solutions, think critically and analytically, be able to determine and use appropriate learning resources. The purpose of this study was to determine the effect of applying the problem based learning method in increasing understanding of the concept of learning outcomes for 21 students of class XII science in Genetics. The subjects in this study were students of class XII science. The type of research conducted is in the form of Classroom Action Research (CAR) by following the syntax of Kemmis and Taggart, covering four stages, namely: 1) planning (planning); 2) implementation (acting); 3) observation and 4) reflection. Learning outcomes data were obtained through written tests before and after learning. The results of this study indicate that the learning outcomes of students in class XIIIPA MAS YASPI Labuhan Deli after learning Problem Based Learning experienced an increase in learning outcomes on Genetic Materials, the results showed an increase in student understanding from the comparison between the first meeting and obtained an average score of 50 and the second meeting obtained a score of average 80 point. Key words: Classroom Action Research, PBL Learning Model, Concept Understanding.   ABSTRAK Problem based learning (PBL) adalah model pembelajaran yang dipicu oleh permasalahan, yang mendorong siswa untuk belajar dan bekerja kooperatif dalam kelompok untuk mendapatkan solusi, berpikir kritis dan analitis, mampu menetapkan serta menggunakan sumber daya pembelajaran yang sesuai. Tujuan penelitian ini untuk mengetahui  pengaruh penerapan metode Problem based learning dalam peningkatan pemahaman konsep hasil belajar siswa kelas XII IPA sebanyak 21 siswa pada Materi Genetika. Subjek dalam penelitian ini merupakan siswa kelas XII IPA. Jenis penelitian yang dilakukan berupa Penelitian Tindakan Kelas (PTK) dengan mengikuti sintaks dari Kemmis dan Taggart, meliputi empat tahapan yaitu: 1) perencanaan (planning); 2) pelaksanaan (acting); 3) pengamatan (observing) dan 4) refleksi (reflecting). Data hasil belajar diperoleh melalui tes tertulis sebelum dan sesudah pembelajaran. Hasil penelitian ini menunjukkan bahwa hasil belajar siswa kelas XIIIPA MAS YASPI Labuhan Deli setelah pembelajaran Problem Based Learning mengalami peningkatan  hasil belajar pada Materi Genetika didapatkan hasil peningkatan dari pemahaman siswa dari perbandingan antara pertemuan I dan didapatkan rata-rata nilai sebanayak 50 serta pertemuan II  didapatkan nilai rata-rata 80. Kata kunci: Penelitian Tindakan Kelas, Model Pembelajaran PBL, Pemahaman Konsep.